A study to determine age at menarche in adolescent school girls of Indore city, M. P. India - Dr. Sunita Solanki; Dr. Ajay Soni; Dr. Vesti Randa; Dr. Ramkrishna Choudhary (International Journal of Medical Research and Review, 2021)
Background: Menarche is a significant milestone in women’s life. It affects the reproductive health and well being of women. This study aims to find out the age at menarche of adolescent girls of Indore city and its relation to various factors. Method: This was a cross-sectional study conducted in six schools of urban areas of Indore city the study group included 492 school girls of age 11 to 18 years. After taking written informed consent from the parents, data was collected on the date of birth, family size, birth order, dietary intake, social-economic status, menarcheal age. Anthropometric measurements were done and data was analyzed. Results: Mean age at menarche was found to be 13.2+1.24 years. It was found to be significantly associated with socioeconomic status, BMI and birth order. Conclusion: The mean age at menarche in this study is comparable to that found in other Indian studies. It is found to be significantly associated with BMI and socioeconomic status of the girls